The EU’s response to Russian hybrid threats - Agyeman, Nana Osei Kojo (2024)
This paper evaluates how the EU has responded to Russian hybrid threats and the efficiency of the counter measures taken in between 2010 and 2024. This qualitative research design is comprised of secondary data which consists mainly of scholarly articles, official reports from both the EU and the Eu member states themselves as well expert interviews along with mass media publications among others. This wide range data allows for more thorough examination on how the EU has countered hybrid threats suspected to have been used by Russia such as energy coercion, disinformation campaigns and political interference. The thesis also mentions recent sanctions imposed on Russia by the European Union referred to as thirteen packages, it will further investigate what sectors were targeted by these bans. The research takes a deep dive into EU policies over time thus giving more insights on how these strategies have been implemented executed so far in order foster understanding about resilience building against hybrid warfare within European countries. It brings out various factors that have affected its responses both from within and without pressures. Lastly, recommendations are made here regarding what ought to be done next to protect the EU against this kind of attacks while at same time adding value to international security discourse and policy making.